Drivers of the Quality of Electricity Supply - Tehero, Remy; Aka, Emmanuel Brou (International Journal of Energy Economics and Policy, 2020)
Although electricity quality is an important input for development and growth, the literature about its determinants quality is scarce. Therefore, this article is the first proposing a cross-country analysis identifying the determinants of the quality of electricity supply at a global level. In this analysis, 138 countries at different development stages have been considered and data are sourced in the Global Competitiveness Report (2016-2017), Worldwide Governance Indicators (WGI) and the World Development Indicators (WDI). The Findings confirm the importance institutional infrastructures such as regulation quality, government effectiveness and rule of law, but also other parameters such as, Foreign Direct Investment and Technology Transfer, Availability of Latest Technology, the income of the population (gdp per capita) and the quality of the workforce (quality of education). The coherence of this empirical result is confirmed by the performances of developing countries which are lower than those of developed countries. Keywords: Electricity quality, Institutions, Investment, Technology JEL Classifications: O30, Q40, Q48 DOI: https://doi.org/10.32479/ijeep.9378